A report to an academy: On carnophallogocentrism, pigs and meat-writing. (May 2016) - Sayers, Janet Grace
How can organisational studies theory respond to the call of nonhuman animals? This article argues there is 'too much humanism' in organisational studies and defines the problem as originating in language practices. The example of factory-farmed pigs is used to illustrate the argument. Derrida's term carnophallogocentrism is used to suggest that ethical thinking about the animal be moved from face-to-face encounters through the eyes to the mouth and that by adopting methods used in literature and 'feminist dog-writing' ways can be found to co-constitute human and nonhuman species in academic writing practices. The term meat-writing is offered as a practice of challenging carnophallogocentrism.